Innovative Strategies for Developing Competency-Based Learning Evaluation in Madrasah Ibtidaiyah Under The Independent Curriculum - Eka Wardatul Hayat; Adiyono Adiyono (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
The Merdeka Curriculum demands changes in the learning evaluation system, especially in Madrasah Ibtidaiyah, so it is more oriented towards developing student competencies. This study used the Systematic Literature Review (SLR) method with the PRISMA approach, examining 120 relevant articles and filtering them into 15 main articles. This study focuses on identifying innovative strategies for developing competency-based evaluation in accordance with the characteristics of Islamic education in Madrasah Ibtidaiyah. The study results show that competency-based evaluation in Madrasah Ibtidaiyah must consider aspects of validity, reliability, fairness, and differentiation to adapt to the needs of learners. The findings also highlight key challenges, such as limited resources, teacher readiness, and the complexity of individual assessment. A formative assessment approach, evaluation-based technology, and authentic assessment are practical solutions to overcome this. This research contributes to designing an evaluation system that is more adaptive, innovative, and based on the values of Islamic education to support meaningful and sustainable learning for Madrasah Ibtidaiyah students in the era of the Independent Curriculum.